Spatio-temporal patterns of under 5 mortality in Nigeria - Ayoade, Modupe Alake (SSM Popul Health, 2018)
• Under 5 mortality rates in Nigeria are very high. • There are significant variations in under 5 mortality rates across states over time. • There is evidence of statistically significant spatial autocorrelation over time. • Significant reductions are achievable with both state and region specific measures.